2008
DOI: 10.1016/j.sna.2007.10.058
|View full text |Cite
|
Sign up to set email alerts
|

Observations of piezoresistivity for polysilicon in bending that are unexplained by linear models

Abstract: Compliant piezoresistive MEMS sensors exhibit great promise for improved on-chip sensing. As compliant sensors may experience complex loads, their design and implementation require a greater understanding of the piezoresistive effect of polysilicon in bending and combined loads. This paper presents experimental results showing the piezoresistive effect for these complex loads. Several n-type polysilicon test structures, fabricated in MUMPs and SUMMiT processes, were tested. Results show that, while tensile str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…An n-type polysilicon device was used for comparing model predictions to experimental results. This investigation is further described in [13] and [14].…”
Section: B Superposition Model Of Piezoresistivity In Bendingmentioning
confidence: 99%
See 2 more Smart Citations
“…An n-type polysilicon device was used for comparing model predictions to experimental results. This investigation is further described in [13] and [14].…”
Section: B Superposition Model Of Piezoresistivity In Bendingmentioning
confidence: 99%
“…2. The nature of Smith's model precludes a positive-sloped nonlinear resistance curve for a flexure in bending due to the way resistors in parallel combine [13], [14].…”
Section: B Superposition Model Of Piezoresistivity In Bendingmentioning
confidence: 99%
See 1 more Smart Citation
“…Few works have been reported on solid-state piezoresistive displacement sensors fabricated by standard micro-machining processes, where custom fabrication steps are not available to incorporate the conventional piezoresistors into the flexures. In [5], piezoresistive position transducers were fabricated through standard micro-machining processes in a variety of polysilicon beam shapes, where considerable nonlinear behavior was reported for bending beam sensors. In [6], a piezoresistive sensor was micro-machined adjacent to an electrothermal micro-actuator using a standard process with n-type polysilicon.…”
Section: Introductionmentioning
confidence: 99%
“…The geometry is a twin-beam structure separated by air so that the total strain in the polysilicon layer is non-zero. Waterfall et al (2008) demonstrated that the relationship between the bending strain and piezoresistivity of the polysilicon layer is nonlinear. The temperature dependence of the piezoresistivity coeffi cients of the silicon and decoupling the sensor from wafer, are two challenges that need to be addressed for the use of MEMS strain sensors to replace conventional foil gages.…”
Section: Strain Sensormentioning
confidence: 99%